Concussion knowledge among family physicians in Croatia. (19th November 2018) - Herceg, Marko; Kalcina, Linda Lusic; Lusic, Ivo
Aim: The objective of this study was to administer and analyze results of a survey targeting knowledge about concussion symptoms, diagnosis, treatment and expected recovery among family medicine specialists in the Split–Dalmatia County of Croatia.Methods: An electronic survey questionnaire was developed utilizing concepts from previously published studies on concussion knowledge, attitudes and beliefs completed by physicians. The survey was intended to briefly and broadly assess concussion knowledge of Croatian healthcare providers. The first section of the survey included five questions clarifying professional practice, years of experience and experience with concussions; the second section included 15 questions about typical concussion symptoms; the third section included 12 questions focused upon three primary components of concussion knowledge: concussion diagnosis, treatment and recovery.Results: Out of 242 surveys mailed, 81 questionnaires (33%) were completed while 161 respondents (67%) did not answer. Out of the 81 completed surveys, 76 (94%) were returned by family physicians specialist and five (6%) by resident physicians in training. 39 (48%) had treated less than ten patients with concussion during last year: 40 (49%) treated 11–20 patients with concussion; and two (3%) treated greater than 20 patients with concussion during last year. While most responses did accurately reflect knowledge of common symptoms (90–100% correct), there was significant lack of knowledge in three areas: only 19% of participants stated that diagnosis of concussion does not require loss of consciousness; three quarters of respondents believed that a diagnosis of concussion requires direct contact to the head and 83% of the respondents believed that persistent subjective complaints are always the result of a more severe initial injury.Discussion: This is the first investigation conducted in Croatia to examine knowledge of concussion diagnosis, as well as the management practices held by medical professionals. Overall, the findings suggest that the knowledge and management practices among family doctors in the region are not consistent with current worldwide views and recommendations. There was not an accurate knowledge of concussion diagnosis, treatment, recovery and prognosis among family physicians. Continued education of medical staff to better identify concussion and increased reliance on objective methods for managing concussion will improve patient management and outcome.